The Role of Adaptive Sales in Increasing the Performance ff Jimshoney Product Sales Personnel in East Java - Rezza Lutviana Suryahadi; Muhadjir Anwar (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
This research is based on the phenomenon of selling online-based products by using salespeople as marketing subjects, so there is a need for research on sales force performance to measure the effectiveness of sales force performance in marketing company products. The purpose of this study was to test and determine the causal relationship between constructs in the model, namely the construct of customer orientation and sales soft capability on the performance of employees with adaptive sales as a mediator.This study uses a quantitative approach. The sampling method used is a purposive sampling method with 100 respondents who are JimsHoney salespeople in East Java who have joined as salespeople for at least 3 months on January 1, 2021. The data analysis used in this study uses Smart PLS version 3 for windows.The conclusion of the study shows that customer orientation has a positive and significant effect on the performance of salespeople for JimsHoney products in East Java, while sales soft capability has no positive and significant effect on the performance of salespeople for JimsHoney products in East Java. Furthermore, customer orientation and sales soft capability have a positive and significant impact on the performance of salespeople through adaptive selling of JimsHoney products in East Java.